Foreign training in Jordan’s international hotel chains: a quantitative investigation - Samer Al-Sabi; Mousa Masadeh; Bashar Maaiah; Mukhles Al-Ababneh (Tourism & Management Studies)
This paper draws on the perceptions of middle managers in Jordan to identify what determines upper management’s decision in International Hotel Chains (IHC) to invest in out-of-country training (OCT). A model employing the presence of relationships between ‘attitudes’, ‘benefits and usefulness’, ‘barriers’ and ‘IHC’s decision’ to invest in OCT, was proposed and examined. A total of 261 middle managers from IHCs in Jordan provided responses to a structured survey. Confirmatory factor analysis validated the dimensions for each construct. Structural equation modelling (SEM) was used to test the relationships among the four constructs of the study. The results showed a direct relationship between attitudes and benefits/usefulness to IHC’s decision to invest in OCT, and demonstrated the mediating role of attitudes in the inverse r